Inflammatory myopathies: an update for neurologists - André Macedo Serafim Silva; Eliene Dutra Campos; Edmar Zanoteli (Arquivos de Neuro-Psiquiatria)
ABSTRACT Idiopathic inflammatory myopathies (IIM) are a heterogenous group of treatable myopathies. Patients present mainly to the rheumatologist and neurologists, complaining of acute or subacute onset of proximal weakness. Extramuscular manifestations may occur, including involvement of the lungs, skin, and joints. Classically, the diagnosis used to be made based on the creatine kinase level increase, abnormalities in electroneuromyography and presence of inflammatory infiltrates in the muscle biopsy. Recently, the importance of autoantibodies has increased, and now they may be identified in more than half of IIM patients. The continuous clinicoseropathological improvement in IIM knowledge has changed the way we see these patients and how we classify them. In the past, only polymyositis, dermatomyositis and inclusion body myopathy were described. Currently, immune-mediated necrotizing myopathy, overlap myositis and antisynthetase syndrome have been considered the most common forms of IIM in clinical practice, increasing the spectrum of classification. Patients previously considered to have polymyositis, in fact have these other forms of seropositive IIM. In this article, we reviewed the new concepts of classification, a practical way to make the diagnosis and how to plan the treatment of patients suffering from IIM.